STUDI PERENCANAAN PERLUASAN SPAM JARINGAN PERPIPAAN DESA SAMBIGEDE, KECAMATAN. BINANGUN, KABUPATEN BLITAR - Yuris Permana Yoga Utama; Ruli Ariyadi (JURNAL DAKTILITAS, 2022)
Abstract Sambigede Village is one of the villages located in Binangun District which is in the southeast of Blitar Regency City with a distance of about 46 Km. The topography of Blitar in the southeast is a low-lying area, prone to drought, natural disasters and floods. Along with the increasing number of residents, the expansion of the drinking water treatment system network in this village is a problem that needs to be done immediately because the need for clean water continues to increase. Until now, the villagers of Sambigede have actually used village water sources as clean water, but the construction of new houses for the villagers is increasing demands for the addition of a new piping network. This study aims to improve the clean water services needed by the residents of Sambigede village, plan a new pipeline network and calculate the required development budget plan. Based on the geographical conditions and topology of the village, the drinking water pipeline network was built by taking underground water sources with drilled wells to take raw water, pumped it, and flowed it through a transmission pipe, stored in a reservoir (reservoir) and then through a distribution pipe it flowed to the service area. The drilled well with a depth of 40 meters is pumped using a submersible deep well type SQ 3-65 submersible pump with a capacity of 0.8 liters per second, head 92 m, pump outlet 1.25 inch, power 1.5 Kw / 2 x 220 volts / 2900 rpm / 50 Hz . Water from the source is channeled through a 24 meter long transmission network to a reservoir (reservoir) with this capacity of approximately 20.25 cubic meters or about 20,250 liters. From the reservoir, the water is then channeled through a distribution network pipe of 843 meters which is divided into area 1 and area 2. In area 1 there will be the addition of a new pipe with a diameter of 2” dim along 480 m as well as the addition of 4 (four) house channels (SR). connection of houses and area 2 there is the addition of a new pipe of 321 m long. In the plan to expand the clean water network SPAM in Sambigede village, Binangun sub-district, Rp. 200,000,000, - (Two Hundred Million Rupiah) including TAX. Keyword: clean water network, gravity system, reservoir, the transmission pipe, the distribution pipe, the budget plan. Abstrak Desa Sambigede adalah salah satu desa yang terletak di Kecamatan Binangun yang berada di tenggara Kota Kabupaten Blitar dengan jarak sekitar 46 Km. Topgrafi Blitar di bagian tenggara adaIah daerah dataran rendah, rawan kekeringan, bencana aIam dan banjir. Seiring dengan jumlah penduduk yang semakin bertambah perluasan jaringan sistem pengolahan air minum di desa ini menjadi masalah yang perlu segera dilakukan karena kebutuhan air bersih terus meningkat. Hingga saat ini, penduduk desa Sambigede sebenarnya telah memanfaatkan sumber air desa sebagai air bersih akan tetapi adanya pembangunan rumah baru warga desa yang semakin bertambah menuntut untuk penambahan jaringan perpipaan baru. Studi ini bertujuan untuk meningkatkan layanan kebutuhan air bersih yang dibutuhkan warga desa Sambigede, merencanaan jaringan perpipaan baru dan menghitung rencana anggaran biaya pembangunan yang diperlukan. Berdasarkan kondisi geografis dan topologi desa, jaringan perpipaan air minum dibangun dengan mengambil sumber air bawah tanah dengan sumur bor untuk mengambil air baku dipompa dialirkan melalui pipa transmisi ditampung dalam reservoir kemudian melalui pipa distribusi dialirkan ke area pelayanan. Sumur bor dengan kedalaman 40 meter di pompa dengan menggunakan pumpa celup (submersible pump) jenis submersible deep well type SQ 3-65 dengan kapasitas 0.8 liter per detik, head 92 m, pump outlet 1,25 inch, power 1,5 Kw / 2 x 220 volt/ 2900 rpm/ 50 Hz . Air dari sumber dialirkan melalui jaringan transmisi sepanjang 24 meter menuju reservoir dengan kapasitas ini kurang lebih memiliki volume 20,25 meter kubik atau sekitar 20.250 liter. Dari reservoir, selanjutnya air dialirkan melalui pipa jaringan distribusi sepanjang 843 meter yang terbagi dalam area 1 dan area 2. Pada area 1 akan ada penambahan pipa baru dengan diameter 2” dim sepanjang 480 m serta penambahan saluran rumah (SR) sebanyak 4 (empat) sambungan rumah dan area 2 ada penambahan pipa baru sepanjang 321 m. Dalam rencana perluasan SPAM jaringan air bersih di desa Sambigede Kecamatan Binangun diperlukan dana sebesar Rp. 200.000.000,- (Dua Ratus Juta Rupiah) termasuk PPn. Kata kunci: jaringan air bersih, gravity system, reservoir, jaringan transmisi, jaringan distribusi, rencana anggaran biaya.